2022
DOI: 10.3390/metabo12060558
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Bladder Cancer Patients’ Serum Reveals Their Sensitivity to Neoadjuvant Chemotherapy

Abstract: Numerous patients with muscle-invasive bladder cancer develop low responsiveness to cisplatin. Our purpose was to explore differential metabolites derived from serum in bladder cancer patients treated with neoadjuvant chemotherapy (NAC). Data of patients diagnosed with cT2-4aNxM0 was collected. Blood samples were retained prospectively before the first chemotherapy for untargeted metabolomics by 1H-NMR and UPLC-MS. To identify characterized metabolites, multivariate statistical analyses were applied, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…According to serum metabolomic profiles detected by NMR, the levels of three amino acids (glutamine, histidine and valine) in bladder cancer patients decreased markedly after surgery and approached those in healthy controls ( 164 ). In an untargeted study using both NMR and MS, significant increases in glycine and decreases in taurine and glutamine levels were observed in patients resistant to neoadjuvant chemotherapy ( 165 ). Monitoring changes in blood amino acids has also been reported to effectively predict chemotherapy efficacy and survival in patients with hematological malignancies ( 169 , 170 ).…”
Section: Metabolomic Biomarkers For Monitoring Cancer Treatment Effic...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to serum metabolomic profiles detected by NMR, the levels of three amino acids (glutamine, histidine and valine) in bladder cancer patients decreased markedly after surgery and approached those in healthy controls ( 164 ). In an untargeted study using both NMR and MS, significant increases in glycine and decreases in taurine and glutamine levels were observed in patients resistant to neoadjuvant chemotherapy ( 165 ). Monitoring changes in blood amino acids has also been reported to effectively predict chemotherapy efficacy and survival in patients with hematological malignancies ( 169 , 170 ).…”
Section: Metabolomic Biomarkers For Monitoring Cancer Treatment Effic...mentioning
confidence: 99%
“…Recent studies have also revealed that metabolites of nucleotide metabolic pathways can be potential predictors of cancer prognosis. Jung et al divided 18 patients with bladder cancer who received neoadjuvant chemotherapy into sensitive (n = 6) and resistant (n = 12) groups based on their therapeutic response and observed higher serum hypoxanthine levels in the resistant group (P-value < 0.05) (165). Furthermore, elevated serum levels of 1-methyladenosine (a purine nucleotide metabolite) are associated with an increased risk of prostate cancer recurrence (168).…”
Section: Nucleotide Metabolismmentioning
confidence: 99%
“… 617 According to metabolic profiles, taurine, glutamine, glycine and hypoxanthine were potential biomarkers of ladder cancer patients treated with neoadjuvant chemotherapy and pathway enrichment analysis characterized significant alterations were related to amino acid metabolism. 618 Amino acid metabolism seems to be a predominant pathway altered in ladder cancer patients and has potential value in enhancing the efficacy of chemotherapy. Notably, hypotaurine and taurine metabolism, pentose and glucuronate interconversions were the most altered pathway for subcutaneous immunotherapy.…”
Section: Enabling Precision Treatmentmentioning
confidence: 99%
“…Our search yielded two studies that investigated the impact of TURBT on the metabolic profile characteristic of BC using human biofluids (blood serum and urine) [113,114]. Additionally, another study focused on evaluating the impact of submucosal injection of gemcitabine prior to TURBT on both BC and adjacent normal tissue [115], while a separate investigation aimed to identify biomarkers in blood serum for predicting the effectiveness of neoadjuvant chemotherapy in BC [116]. Table 4 provides a concise overview of the biological samples, cases under study, analytical techniques and main findings found in these studies.…”
Section: Human Biofluid and Tissue Studiesmentioning
confidence: 99%
“…Yang et al suggested that histamine could protect against disease relapse whereas thiamine could be related to side effects of the treatment. Zhuang et al employed NMR-and MS-based metabolomics methods to discover metabolic biomarkers for predicting the effectiveness of neoadjuvant chemotherapy (NAC) in MIBC patients [116]. Before the first chemotherapy, blood serum was collected from 18 patients who were scheduled to receive NAC (gemcitabine and cisplatin).…”
Section: Human Biofluid and Tissue Studiesmentioning
confidence: 99%